Chemical modification of nitrile rubber in the latex stage by functionalizing phosphorylated cardanol prepolymer: A bio-based plasticizer and a renewable resource. (March 2019) - Samantarai, Satyajit; Nag, Ahindra; Singh, Nitesh; Dash, Debabrata; Basak, Amit; Nando, Golok B; Das, Narayan Ch
The present investigation deals with the functionalization of acrylonitrile butadiene rubber (NBR) by chemically grafting phosphorylated cardanol prepolymer (PCP) onto its backbone chain. The grafting of PCP onto NBR was accomplished in the latex stage successfully using benzoyl peroxide as the free radical initiator. The functionalized NBR (PCP- g -NBR) is characterized by ultraviolet–visible spectroscopy, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and gel permeation chromatography. PCP- g -NBR exhibited an increase in molecular weight (4.4%) with an increase in the polydispersity. The grafting parameters have been optimized using "Taguchi L9 table" and the optimum conditions were found to be "3 phr of initiator concentration, 15 phr of the PCP concentration, reaction temperature of 70°C and reaction time of 6 h." The percentage grafting and grafting efficiency were calculated to be 7.28 and 80.37%, respectively, under optimum processing conditions. The PCP- g -NBR exhibited a reduction in Wallace plasticity number as well as the Mooney viscosity and an enhanced plasticity retention index (PRI) as compared to neat NBR. The rheological measurements exhibited a higher flow behavior index for PCP- g -NBR than the NBR itself. Differential scanning calorimetry and dynamic mechanical analysis results exhibited a decrease in glass transition temperature on functionalization of NBR confirming enhanced plasticization. Thermogravimetric analysis results displayed an increase in thermal stability of the functionalized NBR than that of virgin NBR. The physico-mechanical properties of the PCP- g -NBR vulcanizates were at par with or even better than the neat NBR vulcanizates. 3-(4, 5-Dimethylthiazol-2yl)-2, 5-diphenyltetrazolium bromide assay and hemolysis studies indicated NBR and PCP- g -NBR are nontoxic and biocompatible.